Variation in runoff generation and concentration-discharge behavior in three variably encroached grassland watersheds - Pruitt, Johnny Lee III (My University, 2025)
Displacement of grasses by woody plants, a phenomenon known as woody encroachment, is occurring in grasslands worldwide. Previous studies indicate woody encroachment has the ability to alter runoff generation, increase soil porosity and permeability, decrease soil water residence time, decrease streamflow, and even accelerate soil drying. However, little is understood about the consequences all of these processes have on streamflow sources and composition. To fill this knowledge gap, we deployed high-frequency sampling of stream water during seven different rainstorms during the 2024 water year from three variably-encroached watersheds hosting headwater streams at Konza Prairie Biological Station, a native tallgrass prairie in northeastern Kansas, USA. We also examined streamflow and precipitation records for two time periods, one before widespread encroachment occurred in any of the watersheds (1987-1990) and the other more recently (2020-2023), after significant encroachment. Woody encroachment varies between the watersheds primarily due to differences in the frequency of fire treatment. Upland and riparian woody plant coverage is 6% and 45%, respectively in the annually burned watershed, 20% and 70%, respectively in the biennially burned watershed, and 28% and 74%, respectively in the quadrennially burned watershed. Isotope hydrograph separation analysis based on stream and precipitation stable isotope compositions did not reveal any clear differences in amounts of runoff generation between watersheds. Most of the storms that we sampled were not large enough to cause large changes in stream water isotope compositions. However, our analysis of stream discharge and precipitation records indicates that encroachment is decreasing the sensitivity of streamflow to storms. We examined discharge-precipitation relationships by normalizing the change in streamflow (ΔQ) to precipitation event size (P) and watershed area (A). Results show that ΔQ/P/A values were higher in 2020-2023 than 1987-1990 for all three watersheds, but the difference was greatest for the least encroached watershed, potentially reflecting impacts of climate change on storm intensity coupled with changes in soil permeability as a result of encroachment. Moreover, an analysis of concentration-discharge behavior for stream solutes suggests that encroachment is altering stream composition. Both geogenic and biogenic solutes were more chemodynamic in the least encroached watershed compared to the more encroached watersheds. Additionally, the least encroached had lower pH and higher concentrations of alkalinity and bedrock weathering products, potential in response to encroachment-driven differences in the amount and depth of mineral weathering between watersheds. Taken together, the findings of this study suggest that encroachment is impacting headwater streams not only in terms of their response to storms but also in terms of stream water composition, which can have significant downstream implications for flood risks and water quality.
Keywords: Woody encroachment; Konza; Grassland; Stream; Precipitation; Water